2024
DOI: 10.1007/s10462-023-10660-8
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent deep learning techniques for energy consumption forecasting in smart buildings: a review

R. Mathumitha,
P. Rathika,
K. Manimala

Abstract: Urbanization increases electricity demand due to population growth and economic activity. To meet consumer’s demands at all times, it is necessary to predict the future building energy consumption. Power Engineers could exploit the enormous amount of energy-related data from smart meters to plan power sector expansion. Researchers have made many experiments to address the supply and demand imbalance by accurately predicting the energy consumption. This paper presents a comprehensive literature review of foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Mathumitha et al [26] explored various deep learning methods used for predicting buildings' energy usage and found that the DNN model performed better.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathumitha et al [26] explored various deep learning methods used for predicting buildings' energy usage and found that the DNN model performed better.…”
Section: Related Workmentioning
confidence: 99%
“…Compared to other works, this study concentrates on the predictive modeling of energy consumption in South African residential buildings using RF, DT, XGBoost, and AdaBoost models with real-world data. While the authors in [23][24][25][26] proposed different techniques for predicting the energy consumption of residential buildings, this study investigates whether or not the models we propose outperform their models in terms of prediction accuracy. This will include a detailed analysis of the performance criteria (MSE, MAE, MAPE, and R 2 ) and a discussion on how our findings align with or differ from previous studies.…”
Section: Related Workmentioning
confidence: 99%